Fertility sparing treatment in borderline ovarian tumours - Alvarez, Rosa Maria (Ecancermedicalscience, 2015)
Borderline ovarian tumours are low malignant potential tumours. They represent 10–15% of all epithelial ovarian malignancies. Patients with this type of tumour are younger at the time of diagnosis than patients with invasive ovarian cancer. Most of them are diagnosed in the early stages and have an excellent prognosis. It has been quite clearly established that the majority of borderline ovarian tumours should be managed with surgery alone. Because a high proportion of women with this malignancy are young and the prognosis is excellent, the preservation of fertility is an important issue in the management of these tumours. In this systemic review of the literature, we have evaluated in-depth oncological safety and reproductive outcomes in women with borderline ovarian tumours treated with fertility-sparing surgery, reviewing the indications, benefits, and disadvantages of each type of conservative surgery, as well as new alternative options to surgery to preserve fertility.